O-017 Minimally Invasive Angiographic CT Guided Evacuation of Parenchymal and Ventricular Haemorrhage Using the Apollo System: Proof of Concept in a Cadaver Model. (26th July 2014) - Fiorella, D; Arthur, A
Abstract : Introduction: Apollo (Penumbra Inc, Alameda, CA) is a low profile irrigation-aspiration system designed for the evacuation of intracranial haemorrhage. We demonstrate the feasibility of using Apollo through a minimally invasive approach using angiographic CT guidance. Methods: Parenchymal (n = 1) and mixed parenchymal-intraventricular hematomas (n = 1) were created in cadaver heads using a transvascular (n = 1) or transcranial (n = 1) approach. Hematomas were then imaged with angiographic CT ((ACT), dynaCT, Seimens Medical Imaging, Erlanger, GE) and the long axis of the hematoma defined. The ACT data were then used (iGuide, Siemens Medical Imaging) to guide transcranial access to the hematoma-defining the location of the burr hole and the path to the leading edge of the hematoma. A 8F vascular sheath was then placed under live fluoroscopic guidance into the hematoma. A second ACT was performed to confirm localization of the sheath. The hematoma was then demarcated on ACT and the Apollo system was introduced through the 8F sheath under live fluoroscopic guidance (iPilot, Siemens Medical Imaging). Following irrigation-aspiration with Apollo, repeat ACT was performed to document reduction in hematoma volume. Results: Both transvascular and transcranial techniques were successful in creating intracranial hematomas. Hematomas could be defined with conspicuity sufficient for localization and volumetric measurement using ACT. Live fluoroscopic guidance was effective in navigating a sheath into the leading aspect of a parenchymal hematoma and guiding irrigation-aspiration with the Apollo system. Irrigation-aspiration with Apollo reduced the intracranial haemorrhage volume more than 80% in both cases. The Apollo system was activated for 189 seconds and 300 in the first and second subjects, respectively. Conclusions: The described cadaver model is a useful means by which to study interventional techniques for intracranial haemorrhage. It seems feasible to use ACT to guide the evacuation of parenchymal and intra-ventricular haemorrhages using the Apollo system through a minimally invasive trans-cranial access. Disclosures: D. Fiorella: 1; C; Siemens, Penumbra. A. Arthur: 1; C; Siemens, Penumbra.